2017
DOI: 10.31219/osf.io/k39mn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humans as Superorganisms: How Microbes, Viruses, Imprinted Genes, and Other Selfish Entities Shape Our Behavior

Abstract: Psychologists and psychiatrists tend to be little aware that (a) microbes in our brains and guts are capable of altering our behavior; (b) viral DNA that was incorporated into our DNA millions of years ago is implicated in mental disorders; (c) many of us carry the cells of another human in our brains; and (d) under the regulation of viruslike elements, the paternally inherited and maternally inherited copies of some genes compete for domination in the offspring, on whom they have opposite physical and behavio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
0
16
0
1
Order By: Relevance
“…Recent reports emphasize that the intestinal microflora can affect the outcome of some neurological circumstances, enhancing the occurrence, progression, or deterioration of certain central nervous system (CNS) disorders [5], as well as the extent and the ways in which microbes influence brain physiology, functions, and behavior [4,6]. A bi-directional relationship linking the gut microbiota and the brain along the so-called the microbiotagut-brain axis, contributes to the pathogenesis of certain disorders via the involvement of brain inflammation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports emphasize that the intestinal microflora can affect the outcome of some neurological circumstances, enhancing the occurrence, progression, or deterioration of certain central nervous system (CNS) disorders [5], as well as the extent and the ways in which microbes influence brain physiology, functions, and behavior [4,6]. A bi-directional relationship linking the gut microbiota and the brain along the so-called the microbiotagut-brain axis, contributes to the pathogenesis of certain disorders via the involvement of brain inflammation [7].…”
Section: Introductionmentioning
confidence: 99%
“…With the recent advances made in high-throughput sequencing technologies, researchers are now able to accurately characterise the complex microbial communities that develop within human habitats. The astonishing extent and complexity of these communities that has been revealed in these studies has suggested a level of importance in human health and disease that is only now beginning to be understood, with the "superorganism" or "holobiont" hypotheses being proposed [8]. However, despite the advances being made in this field, attention has largely focussed on the bacterial components of these rich microbial communities.…”
Section: The Role Of the Mycobiome In Relation To Anti-fungal Immunitymentioning
confidence: 99%
“…During our studies, we also asked the question why there are so many NCDs in China. When a large number of literatures focused on the importance of human symbiotic microbiota with NCDs such as obesity, diabetes, hypertension, stroke, cancer, autism, depression [14][15][16][17][18][19][20][21][22][23][24] , we were also attracted by this interesting research field. Following the interesting and valuable studies of Dr. Gordon JI [25][26][27][28] and Dr. Liping Zhao [29][30][31][32][33] on the close relationship between microbiota with obesity, we began to test whether we can control the fat of our own body by controlling the gut flora.…”
Section: Did the Hunger Sensation Come From Gut Flora?mentioning
confidence: 99%